2014
DOI: 10.1016/j.jbusvent.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The value of an educated population for an individual's entrepreneurship success

Abstract: The value of an educated population for an individual's entrepreneurship success Millán, J.M.; Congregado, E.; Román, C.; van Praag, C.M.; van Stel, A.J. Link to publication Citation for published version (APA):Millán, J. M., Congregado, E., Román, C., van Praag, M., & van Stel, A. (2011). The value of an educated population for an individual's entrepreneurship success. (Tinbergen Institute discussion paper; No. TI2011-065/3). Amsterdam/Rotterdam: Tinbergen Institute. General rightsIt is not permitted to downl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 109 publications
3
37
1
5
Order By: Relevance
“…This reduces the quality of latent entrepreneurs in the population and reduces the talent available for existing enterprises, limiting their likelihood of success (Millán et al 2014). …”
Section: Entrepreneurship and Survival In The Peripherymentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the quality of latent entrepreneurs in the population and reduces the talent available for existing enterprises, limiting their likelihood of success (Millán et al 2014). …”
Section: Entrepreneurship and Survival In The Peripherymentioning
confidence: 99%
“…For example, the influences from the location may reduce competition and expose entrepreneurs to a culture where the acquisition of wealth and personal success are less important . Equally, locational factors in peripheral regions may be part of a process that leads to a depletion of human capital resources (Kaufmann and Malul 2015;Malul 2015), so that the average latent entrepreneur will be less well placed to exploit available opportunities (Millán et al 2014). …”
Section: Please Insert Figure 1 About Herementioning
confidence: 99%
“…For example Rauch and Rijsdijk [30] and Millán et al [22] showed that higher education can positively influence business performance and according to Wang [36] it can improve management of financial risks.…”
Section: Research Methodology and Datamentioning
confidence: 99%
“…En al ámbito de estudio sobre incidencia de nivel de educación formal en emprendimiento, se ha reconocido que favorece la intención de emprender (Bae et al 2014), que existe vínculo de educación terciaria y emprendimiento de población en EEUU (Millan et al, 2014), también que un mayor nivel educacional incrementa las capacidades técnicas y habilidades del emprendedor (Gomezelj y Antončič, 2008), y que la educación formal previa, favorece los resultados del entrenamiento de emprendedores (Ashourizadeh et al, 2014). Respecto del tamaño de empresa, Kotey y Folker (2007) muestran que, en contexto de Pymes, las empresas más pequeñas, presenta menor propensión a la capacitación formal y que emprendimientos de menor tamaño se orientan hacia el aprendizaje informal.…”
Section: Marco Teóricounclassified
“…UU. (Millan et al, 2014) e India (Rauth, 2014). Se estima que existe brecha de conocimiento de esta temática en Chile y Latinoamérica, y que no se ha estudiado con mayor profundidad, las implicancias de número de socios y fuente de financiamiento sobre resultados de capacitación.…”
Section: Marco Teóricounclassified